Oju and Inu: solidarity in the informal market space in Ibadan, Nigeria. (2019)
Informal markets provide employment for a large spectrum of Nigerians. These markets provide access to livelihood for those willing to work within the market environment and operate within its rules. A major normative value, which also spells out the ethics in the informal market space, is solidarity-in-completion. Indeed, traders are in competition, but they also solidarize for individual and market progress. This article examines the context of solidarity in informal markets in Ibadan, Nigeria. The study was guided by the Asuwada theory of sociation, which explains the context of solidarity as ethical in traditional societies. Qualitative data were collected through 12 key informant interviews, 60 in-depth interviews, six focus group discussion sessions, and 12 case studies. Access to space and retention of such space in the market is structured by the local contexts of oju and inu relations that determine and contextualize solidarity, and normative solidarity regulates competition among traders.